Edukasi Penanganan Cidera OlahragaSprain Ankle Pada Atlit Wushu di Surabaya - Yohanes Deo Fau; Angria pradita; sartoyo; Ahmad Abdillah Iqbal; Ester Popy Bove (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2026)
Sports injuries, particularly ankle sprain, are among the most common injuries experienced by Wushu athletes and may affect athletic performance and participation in training and competition. This community service activity aimed to improve athletes’ knowledge regarding the identification, initial management, and prevention of ankle sprain injuries. The activity was conducted at Dojo Wushu Yasanis Surabaya involving 67 Wushu athletes aged 7–20 years. The implementation method consisted of problem identification, preparation of educational materials, pre-test, educational intervention, discussion session, and post-test. Knowledge evaluation was carried out using a Google Form containing 10 multiple-choice questions administered before and after the educational session. The educational material covered the definition of ankle sprain, injury mechanisms, signs and symptoms, initial management, and injury prevention strategies. The results showed a substantial increase in participants’ knowledge after the intervention. The average pre-test score was 35.07, while the average post-test score increased to 97.76. The findings indicate that educational intervention effectively improved participants’ understanding of ankle sprain management. Therefore, similar educational programs may be implemented routinely to support injury prevention and improve sports health literacy among athletes.